Reflections on climate change communication research and practice in the second decade of the 21st century: what more is there to say?. (5th April 2016) - Moser, Susanne C.
Abstract : Appreciable advances have been made in recent years in raising climate change awareness and enhancing support for climate and energy policies. There also has been considerable progress in understanding of how to effectively communicate climate change. This progress raises questions about the future directions of communication research and practice. What more is there to say? Through a selective literature review, focused on contributions since a similar stock‐taking exercise in 2010, 1 the article delineates significant advances, emerging trends and topics, and tries to chart critical needs and opportunities going forward. It describes the climate communication landscape midway through the second decade of the 21st century to contextualize the challenges faced by climate change communication as a scientific field. Despite the important progress made on key scientific challenges laid out in 2010, persistent challenges remain (superficial public understanding of climate change, transitioning from awareness and concern to action, communicating in deeply politicized and polarized environments, and dealing with the growing sense of overwhelm and hopelessness). In addition, new challenges and topics have emerged that communication researchers and practitioners now face. The study reflects on the crucial need to improve the interaction between climate communication research and practice, and calls for dedicated science‐practice boundary work focused on climate change communication. A set of new charges to climate communicators and researchers are offered in hopes to move climate change communication to a new place—at once more humble yet also more ambitious than ever before, befitting to the crucial role it could play in the cultural work humanity faces with climate change. WIREs Clim Change 2016, 7:345–369. doi: 10.1002/wcc.403 This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Communication